2020
DOI: 10.3389/fimmu.2020.01923
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Primary Immunodeficiency Diseases in Malaysia: 1979–2020

Abstract: Introduction: Primary immunodeficiency diseases (PIDs) are under-reported in Malaysia. The actual disease frequency of PID in this country is unknown due to the absence of a national patient registry for PID. Objective: This systematic review aimed to determine the prevalence rates of PID cases diagnosed and published in Malaysia from 1st of January 1979 until 1st of March 2020. It also aimed to describe the various types of PIDs reported in Malaysia. Method: Following the development of a comprehensive search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…2 Department of Paediatrics, UKM, Kuala Lumpur, Malaysia. 3 Pantai Hospital, Kuala Lumpur, Malaysia. 4 Department of Paediatrics, Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, Selangor, Malaysia.…”
Section: Fundingmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Department of Paediatrics, UKM, Kuala Lumpur, Malaysia. 3 Pantai Hospital, Kuala Lumpur, Malaysia. 4 Department of Paediatrics, Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, Selangor, Malaysia.…”
Section: Fundingmentioning
confidence: 99%
“…A study in the United States (US) estimated the incidence of CGD is between 1 in 200,000 to 1 in 250,000 live births [ 2 ]. A systematic review on published primary immunodeficiency disease (PID) in Malaysia showed that CGD was the third most common reported form of PID, which is comparable with Singapore’s PID cohort [ 3 ]. Chronic granulomatous disease cases in Malaysia were first reported in 1994 diagnosed in two unrelated boys [ 4 ] based on nitroblue tetrazolium dye test (NBT) and chemiluminescence assay (CA); and this would have been the first report from South East Asia (SE Asia).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several case reports 11–15 and a clinical epidemiology study 4 of PID in this country. A very recent article has reported that the prevalence of PID in Malaysia was 0.37 per 100 000 population 16 . This rate was very much lower than the published rates in other countries, which range from 4.4 to 20.27 per 100 000 population.…”
Section: Introductionmentioning
confidence: 76%
“…Chronic granulomatous disease cases in Malaysia were rst reported in 1994 that was diagnosed in two unrelated boys [4] based on nitroblue tetrazolium dye test (NBT) and chemiluminescence assay (CA) which would have been the earliest patient reported from South East Asia (SE Asia). Few countries in SE Asia (Malaysia, Singapore and Thailand) have published reports of case series of PID which included CGD [3][4][5][6][7]. This report would be the earliest patient series in SE Asia, revealing some inherent differences in the clinical and demographic patterns from the Europe, America or Asia (8,9) Methods Malaysia Primary Immunode ciency Network (MyPIN) is a collaborative network of clinical immunologists, immunopathologists, scientists and general pediatrician/physicians managing primary immunode ciency patients in both government and academic institutions.…”
mentioning
confidence: 99%